A new technique for syndesmotic screw placement in ankles (Annals of Medical Research, 2023)
Aim: Screw used in the treatment of ankle syndesmosis diastasis can be placed in malposition. Our aim in the study is to define a new technique for sending the screws in the right direction.Materials and Methods: The ankle tomography of 188 patients was evaluated. First, the medial malleolus root was divided into three equal parts in axial CT section. Then, a screw model was drawn to fit the fibula to the concave surface in the tibia in another axial CT section where the syndesmosis joint is prominent.These two axial CT sections were placed on top of each other with computer program. Results are notedResults: While 95.7% of the screw simulations were passing through the front 1/3, 4.3% through the middle 1/3, the screw did not pass through the rear 1/3 in any simulation. 187 of these lines passed between the most lateral peak of the fibula and 3 mm posterior.Conclusion: During diastasis surgery, the insertion site of the drill should be chosen between the sharp peak of the fibula and the 3mm posterior. When the drill is placed in this way and directed 1/3 anterior to the medial malleolus, our screw will be sent in the correct position. Our study revealed that the surgical treatment of syndesmos dissociation with screws is a landmark independent of the patient's position and the skill of the surgeon.  There is no other study like this study. However, considering the consistency of our results with the literature, we believe that our study can guide surgeons in practical applications.
Keywords: Syndesmosis; Syndesmosis diastasis; Screw placement; Ankle trauma; Computed tomography